Optimization of Nano Hydroxyapatite/chitosan Electrophoretic Deposition on 316L Stainless Steel Using Taguchi Design of Experiments - Kadhim, Mohammed Jasim; Abdullatef, Nawal Ezzat; Abdulkareem, Makarim Hazim (Al-Nahrain Journal for Engineering Sciences, 2017)
The aim of this work is to determine the optimum parameters for deposition of chitosan and mixture of chitosan and hydroxyapatite (HA) layers using electrophoretic deposition. The layers were on 316L stainless steel substrate. Taguchi approach was utilized to select the optimum parameters for both layers. The parameters used for deposition chitosan are voltage, time and temperature while the parameters used for HA and chitosan are voltage, time, concentration and temperature. Zeta potential tests were employed to measure the solutions stability. Coating layers were characterized for thickness, porosity and nanoroughness using optical microscopy (OM) and atomic force microscopy (AFM). The results from Taguchi design of experiments demonstrated that the best conditions for deposition of chitosan and HA layers are 50 V, 5 min, 3 g HA/L and 30°C. The corresponding thickness, % porosity, nanoroughness and microroughness for optimum conditions were 22 µm, 3.53, 4.48 nm and 3.85 µm respectively.